Main Ways of Development of Iran’s Military Policy after the Lifting of International Sanctions - A, Makangali B. (Farabi Journal of Social Sciences, 2019)
Abstract. This article deals with the Iranian military policy after the removal of sanctions from Tehran at the beginning of 2016, which was made possible due to an agreement on the Iranian nuclear program with the help of six international mediators (USA, France, Britain, Germany, China and Russia). The main objective of this w ork is to trace and analyze the main directions of development of military and defense policy of Iran in the new geopolitical conditions. Since after signing agreement on the nuclear program, on the one hand, Tehran has to abandon its unconventional weapons, which since the Shah’s time was seen as a means to achieve regional hegemony and deterrence factor. On the other hand, the Iranian leadership now faces the challenge to achieve the same purposes, though by other means, including army modernization, qualitative upgrade of weapons, purchase of modern systems and strengthening its own military-industrial complex, etc. All these processes concern the safety of the nearest regional neighbors of Iran. Therefore, the article presents the forecasts of possible consequences of these trends in the development of international relations and regional security in the Persian Gulf. Key words: Iran’s nuclear program, Iran’s missile program, sanctions, weapons, defense policy, military exercises, conflict.